Effect of an Early Oral Food Intake Strategy on the Quality of Life of Postoperative Patients With Esophageal Cancer - Yang, Renmei; Yuan, Wenxiu; Li, Zhengfang; Yang, Manrong; Jiang, Yuequan (Frontiers in Surgery, 2022)
Objective: To explore the early oral food intake on the quality of life of postoperative patients with esophageal cancer. Methods: A total of 100 patients with esophageal cancer were randomized into an observation group and a control group, with 50 patients in each group. The patients in the control group were routinely indwelt with a gastric tube and fasted for seven days. If no abnormality was found in examinations, the patients were instructed to attempt drinking water and gradually try eating liquid, semi-liquid, and common foods. The patients in the observation group were subjected to the early oral food intake strategy. The recovery and gastrointestinal symptoms of the patients were evaluated using the six-minute walk test and gastrointestinal symptom rating scale (GSRS) at discharge. The quality of life of patients was evaluated using the QLQ-C30 scale and QLQ-OES18 scale during the return visit to the hospital one month after discharge. Results: The GSRS score of the observation group was markedly lower than that of the control group. The six-minute walk distance in the observation group was significantly higher than that in the control group; the difference was statistically significant (P < 0.01). In comparing the QLQ-C30 scores of the two groups, the scores in physical function, emotional function, and general health condition in the observation group were higher than those in the control group. In comparing the QLQ-OES18 scores of the two groups, the scores in dysphagia, eating, reflux, pain domains, and choking symptoms in the observation group were lower than those in the control group; the differences were statistically significant (P < 0.01), and there were no statistically significant differences in other symptoms and related functions between the two groups (P > 0.05). Conclusion: The early oral food intake strategy can reduce gastrointestinal symptoms, promote recovery of postoperative patients with esophageal cancer, and improve quality of life.